ISDC Reflections on Emerging One CGIAR Research Portfolio and Investment Plan - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2021)
The Executive Management Team (EMT) requested the Independent Science for Development Council (ISDC) to comment on the preliminary set of Research Initiatives. The rapid evolution of the Investment Plan presents limited information and time to review. Therefore, this document provides brief reflections that used additional information such as material from the 12th CGIAR System Council Meeting and learnings shared from the ISDC Investment Advisory Group (IAG) members.